(untitled) (Eurasian Medical Research Periodical, 2025)
In this work, histological changes in alveolocytes in chronic bronchitis are investigated. Chronic bronchitis is a long-term inflammatory disease of the respiratory tract that can significantly alter the structure of lung tissue. Histological analysis of alveolar cells, such as type I and type II alveolocytes, plays a key role in assessing changes occurring at the cellular level in this disease. As a result of prolonged inflammation and hypoxia, changes in their morphology may occur, including thickening of the alveolar membranes, a decrease in the number of type II alveolocytes, which disrupts surfactant synthesis and leads to a deterioration in gas exchange. These changes can contribute to the progression of the disease and the development of respiratory failure. An important aspect is also the assessment of the interaction of alveolocytes with inflammatory cells and their role in the pathogenesis of chronic bronchitis. The study of these changes allows us to better understand the mechanisms of the disease and open up new ways for diagnosis and treatment.